Structural and regulatory determinants of flagellar motility in Rhodobacterales—the archetypal flagellum of Phaeobacter inhibens DSM 17395 - Jürgen Tomasch; Pascal Bartling; John Vollmers; Lars Wöhlbrand; Michael Jarek; Manfred Rohde; Henner Brinkmann; Heike M. Freese; Ralf Rabus; Jörn Petersen (mSystems)
ABSTRACT Flagellar motility is crucial for the swim-and-stick lifestyle and plays an important role in bacterial-algal interactions of Rhodobacterales. This alphaproteobacterial order contains three distinct types of flagellar gene clusters (FGCs) for the formation of a functional flagellum. Our phylogenetically broad taxon sampling of more than 300 genomes revealed that the most common FGC, the fla1-type, was probably already present in the common ancestor of Rhodobacterales and was strictly vertically inherited, while the other two FGC types, fla2 and fla3, were spread via horizontal operon transfers. Swimming of the marine model organism Phaeobacter inhibens DSM 17395 (Roseobacteraceae) is mediated by the archetypal fla1-type flagellum. Screening of 13,000 transposon mutants of P. inhibens on soft agar plates revealed that 40 genes, including four genes encoding conserved but not yet characterized proteins (CP1–4) within the FGC, are essential for motility. Exoproteome analyses indicated that CP1–4 are required at different stages of flagellar assembly. Only eight genes outside the FGC were identified as essential for swimming motility, including all three genes of the CtrA phosphorelay. Using comparative transcriptomics of ΔcckA, ΔchpT, and ΔctrA mutants of the distantly related model organisms P. inhibens and Dinoroseobacter shibae DSM 16493, we identified genes for the flagellum and cyclic di-GMP turnover as core targets of the CtrA phosphorelay and a conserved connection with quorum sensing across members of the Rhodobacterales.IMPORTANCEThe bacterial flagellum is a sophisticated nanomachine for swimming motility and rapid chemotactic response to gradients of attractants or repellents in the environment. It is structurally highly conserved and has been intensively studied in gammaproteobacterial model bacteria such as Escherichia coli and Salmonella enterica. However, the flagellar gene clusters of different alphaproteobacterial orders have distinct structures and compositions, as demonstrated by the three flagellar systems of Rhodobacterales investigated in the current study. The archetypal fla1-type flagellum originated in its common ancestor and evolved synchronously with the host. The universal presence of four as yet uncharacterized essential genes in fla1-type FGCs (CP1–4) reflects the order-specific adaptation of the flagellar system during bacterial evolution. Comparative transcriptome analyses of ΔcckA, ΔchpT, and ΔctrA mutants showed that the core function of the CtrA phosphorelay in Rhodobacterales is the transcriptional control of flagellar genes.